2006
DOI: 10.1016/j.ejvs.2006.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamics in Symptomatic and Asymptomatic Patients with Severe Unilateral Carotid Stenosis before and after Carotid Endarterectomy

Abstract: The exhausted ability of cerebral autoregulation is an important factor differentiating between symptomatic and asymptomatic patients with severe carotid stenosis. Successful surgery provides good recovery of cerebral hemodynamics in both symptomatic and asymptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
4
19
1
Order By: Relevance
“…However, patients with symptomatic carotid artery stenosis may lack adequate collateral circulation and experience strokes or transient ischemic attacks; 4,21,2527 these patients rely more heavily on reducing peripheral cerebral resistance to maintain adequate perfusion of the cerebral hemispheres. 20,34,36 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with symptomatic carotid artery stenosis may lack adequate collateral circulation and experience strokes or transient ischemic attacks; 4,21,2527 these patients rely more heavily on reducing peripheral cerebral resistance to maintain adequate perfusion of the cerebral hemispheres. 20,34,36 …”
mentioning
confidence: 99%
“…22 The PI is often documented to be ≥ 1.0 in asymptomatic CEA patients and < 1.0 in symptomatic CEA patients, indicating reduced peripheral cerebral resistance and likely a degree of cerebral autoregulatory exhaustion. 31,34,36,38 Symptomatic patients with a baseline PI < 1.0 prior to CEA often demonstrate increased CBF after plaque removal and flow restoration. 5,6,19,20,30,31,34,3638 …”
mentioning
confidence: 99%
“…These observations are in line with previously published results by Telman and Reinhard. 18,20, 21 It may be argued that abrogation of carotid artery stenosisevoked cerebral hypoperfusion by CEA is critically involved in the improvement of cerebral autoregulation. However, the improvement of autoregulation was independent of changes in cerebral blood flow indicating differential mechanistic and etiological effects of CEA on cerebral function and hemodynamics.…”
Section: Cea and Baroreflex Sensitivitymentioning
confidence: 99%
“…15 Cerebral autoregulation is impaired in carotid artery stenosis [16][17][18][19] and is partly restored by CEA. 20, 21 In the present study, we aimed to verify the short-term effect of CEA on BRS using a novel statistical algorithm specifically validated for baroreflex calculation. 22, 23 Furthermore, we assessed cerebral autoregulation in patients with carotid artery stenosis before and after CEA.…”
Section: Editorial P 2058mentioning
confidence: 99%
“…Many authors reported that the identification of a given degree of stenosis alone is no longer sufficient to identify patients at high risk for developing stroke [16,17,18,19]. Ultrasound can determine the so-called vulnerable plaque by estimation of its echolucency or the presence of an irregular surface.…”
Section: How Should the Degree Of Carotid Stenosis Be Assessed?mentioning
confidence: 99%